Maimonides Review of Philosophy and Religion Volume 4, 2025 - Torbidoni, Michela (Maimonides Review of Philosophy and Religion, 2025)
The Maimonides Review of Philosophy and Religion is an annual collection of double-anonymous peer-reviewed articles that seeks to provide a broad international arena for an intellectual exchange of ideas between the disciplines of philosophy, theology, religion, cultural history, and literature and to showcase their multifarious junctures within the framework of Jewish studies. Contributions to the Review place special thematic emphasis on scepticism within Jewish thought and its links to other religious traditions and secular worldviews. The Review is interested in the tension at the heart of matters of reason and faith, rationalism and mysticism, theory and practice, narrativity and normativity, doubt and dogma.